The genetic diversity of reed canarygrass (Phalaris arundinaceae L.) assessed by isozyme markers - R. S. Yudina; E. K. Khlestkina (Вавиловский журнал генетики и селекции, 2016)
The reed canarygrass (Phalaris arundinacea L.) is a wild-growing rhizomatous perennial cereal plant. This is a valuable forage and decorative crop, widely spread over all the continents except for Antarctic. So far, the reed canarygrass has become rather demanded in many European countries as a source of bioenergy. Among the major advantages of the reed canarygrass are high biomass yield, ecological stability, tolerance, and high seed production. Similar to most of wild-growing plants, the reed canarygrass is poorly studied. In the current study, the genetic diversity of a reed canarygrass collection (42 populations collected in meadow biocenoses of several regions in Russia and some other countries) was investigated using isozyme markers IDH (isocitrate dehydrogenase), GDH (glutamate dehydrogenase), MDH (malate dehydrogenase), ME (malic enzyme), and SKDH (shikimate dehydrogenase). Genetic control of these enzymes was determined in reed canarygrass for the first time. IDH and ME are controlled each by one locus (Idh and Me, respectively), SKDH and GDH have digenic control (loci Skdh1 and -2; Gdh1 and -2, respectively), MDH is controlled by 3 loci (Mdh1, -2 and -3). A number of alleles per locus varied from 1 to 3. High activities in different organs and tissues, as well as codominant inheritance make isozymes convenient genetic markers in various studies into ecological and population genetics, especially in plant species, like reed canarygrass, with unsequenced genome. Cluster analysis based on isozyme data distinguished 22 diverse groups. The degree of genetic similarity was not related with geographical origin of the material.